2015
DOI: 10.1002/jsfa.7369
|View full text |Cite
|
Sign up to set email alerts
|

The effects of muffins enriched with sour cherry pomace on acceptability, glycemic response, satiety and energy intake: a randomized crossover trial

Abstract: CP may be a good functional ingredient for bakery products that assists in managing glucose levels, satiety, and subsequent energy intake in healthy individuals. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…Thus, mango by-products (Aziah et al, 2011;Ramirez-Maganda et al, 2015;Sudha et al, 2015), grape by-products (Walker at al., 2014;Mildner-Szkudlarz et al, 2015), sour cherry pomace (Bajerska et al, 2016), berry pomace (Mildner-Szkudlarz et al, 2016) apple skins (Rupasinghe et al, 2008(Rupasinghe et al, , 2009, apple pomace (Sudha et al, 2016), green banana flour (Segundo et al, 2017), orange fibers (Romero-López et al, 2011), date fruit fiber concentrates (Mrabet et al, 2016), carrot pomace (Maazobi et al, 2016), pumpkin seed flour (Bialek et al, 2016), hazelnut skin (Cikrikci et al, 2016) and potato peel (Arora and Camire, 1994;Ben Jeddou et al, 2017) have been studied. In Table 2, a partial listing of papers on practical uses of FVB in cakes is shown.…”
Section: Cakesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, mango by-products (Aziah et al, 2011;Ramirez-Maganda et al, 2015;Sudha et al, 2015), grape by-products (Walker at al., 2014;Mildner-Szkudlarz et al, 2015), sour cherry pomace (Bajerska et al, 2016), berry pomace (Mildner-Szkudlarz et al, 2016) apple skins (Rupasinghe et al, 2008(Rupasinghe et al, , 2009, apple pomace (Sudha et al, 2016), green banana flour (Segundo et al, 2017), orange fibers (Romero-López et al, 2011), date fruit fiber concentrates (Mrabet et al, 2016), carrot pomace (Maazobi et al, 2016), pumpkin seed flour (Bialek et al, 2016), hazelnut skin (Cikrikci et al, 2016) and potato peel (Arora and Camire, 1994;Ben Jeddou et al, 2017) have been studied. In Table 2, a partial listing of papers on practical uses of FVB in cakes is shown.…”
Section: Cakesmentioning
confidence: 99%
“…From a nutritional perspective, all studies have shown an increase in fiber and polyphenols with the addition FVB. Added to that, the in vivo glycemic response was reduced with the incorporation of FVB (Aziah et al, 2011;Romero-López et al, 2011;Ramirez-Maganda et al, 2015;Bajerska et al, 2016). This may be due to the incorporation of soluble fibers with thickening properties, especially in the study of Romero-López et al (2011), who added orange fiber, which is rich in pectin.…”
Section: Nutritional Improvement Of Cakes Through the Utilization Of Fvbmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, PP has not been studied as an ingredient for enriching other related formulations such as sponge and layer cakes. Cakes may be good carriers for these by‐products, thus providing valuable healthy components to the diet (Jung et al ., ; Younas et al ., ; Bajerska et al ., ; Khalifa et al ., ; Mildner‐Szkudlarz et al ., ). However, it must be taken into account that the physical properties of pomace and mainly its particle size may influence the technological quality of the final product (De la Hera et al ., ; Dhen et al ., ; Majzoobi et al ., ).The objectives of the present work were to assess ground PP as a rich fibre ingredient for sponge and layer cakes.…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions were reached by Savastano et al (2014) and Ye et al (2015), who proved that an addition of dietary fibre to food significantly increased the feeling of satiety and reduced appetite after its consumption. In turn, Bajerska et al (2016) examined the effect of adding sour cherry pomace (CP), the by-product obtained during fruit processing, to the production of muffins to replace wheat flour, applying it in different shares. It was observed that enrichment of the baking mix with 20 and 30% share of CP increased the satiety potential of those products and created a lower supply of energy related to their consumption.…”
Section: Discussionmentioning
confidence: 99%